Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1088/1748-9326/ab21e7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of black carbon aerosols: the role of shortwave cloud feedback

Abstract: Using idealized climate model simulations, we investigate the effectiveness of black carbon (BC) aerosols in warming the planet relative to CO 2 forcing. We find that a 60-fold increase in the BC aerosol mixing ratio from the present-day levels leads to the same equilibrium global mean surface warming (∼4.1 K) as for a doubling of atmospheric CO 2 concentration. However, the radiative forcing is larger (∼5.5 Wm −2 ) in the BC case relative to the doubled CO 2 case (∼3.8 Wm −2 ) for the same surface warming ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…We define efficacy as the relative change in GSAT induced by a forcing agent compared to carbon dioxide, for an equivalent perturbation in global mean energy balance at the top of the atmosphere (TOA) or tropopause. Previous studies have indicated that the efficacies of different forcing agents may vary significantly from unity (Hansen et al, 2005;Manabe & Stouffer, 1980;Marvel et al, 2015;Modak et al, 2016;Modak et al, 2018;Modak & Bala, 2019;Shindell, 2014;Shindell et al, 2015;Stuber et al, 2005). Hansen et al (2005) showed that in a single model, efficacies varied widely across many forcing agents, identifying an efficacy of ~1.5 for methane and ~0.6 for black carbon (BC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We define efficacy as the relative change in GSAT induced by a forcing agent compared to carbon dioxide, for an equivalent perturbation in global mean energy balance at the top of the atmosphere (TOA) or tropopause. Previous studies have indicated that the efficacies of different forcing agents may vary significantly from unity (Hansen et al, 2005;Manabe & Stouffer, 1980;Marvel et al, 2015;Modak et al, 2016;Modak et al, 2018;Modak & Bala, 2019;Shindell, 2014;Shindell et al, 2015;Stuber et al, 2005). Hansen et al (2005) showed that in a single model, efficacies varied widely across many forcing agents, identifying an efficacy of ~1.5 for methane and ~0.6 for black carbon (BC).…”
Section: Introductionmentioning
confidence: 99%
“…The ERF framework provides a more complete understanding of the energy budget response to different drivers than more traditional radiative forcing definitions (Hansen et al, 2005;Sherwood et al, 2015) and accounts for some of the differences between GSAT responses to different drivers that were previously accounted for by employing nonunity efficacies. However, some studies using ERF still find efficacies deviating from unity (Marvel et al, 2015;Modak et al, 2018Modak et al, , 2016Modak & Bala, 2019;Shindell et al, 2015). This is further complicated by the fact that there are various methods for calculating ERF in models, which could affect efficacies (Forster et al, 2016;Sherwood et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The 2 m air temperature was higher despite considering the direct aerosol effects of the areas where the long-wave radiation increased by 20 W m −2 and where both coarse and accumulation mode BC exceeded values of 30 ppb. These hotspots might be co-aligned with the BC impacts at certain locations, as the BC influence is known for its localising effects with no clear direct link between the pattern of forcing and the pattern of temperature change (Modak and Bala, 2019). Overall, regardless of the emissions source, the direct radiative forcing and the consequent air temperature increase were estimated for BC by different studies (Ma et al, 2018;Zhuang et al, 2019;Kostrykin et al, 2021), and the cooling effects were also detected (Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Sometimes a cooling effect is also detected (Ma et al, 2018). All of these effects, however, are localised (Modak and Bala, 2019). In Ukraine, there are no observations of carbonaceous aerosols in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…It has, however, been shown that in global climate models the temperature response per unit forcing varies depending on the type of forcing, both in idealized scenarios with abruptly applied forcing (e.g., Hansen et al., 2005 ; Modak & Bala, 2019 ; Modak et al., 2016 , 2018 ; Richardson et al., 2019 ; Shindell et al., 2015 ) and in transient scenarios (e.g., Zhao et al., 2019 ). The concept of forcing efficacy has been introduced to account for these differences in the temperature response (Hansen et al., 2005 ).…”
Section: Introductionmentioning
confidence: 99%